Spatial embeddedness and firm performance: an empirical exploration of the effects of proximity on innovative and economic performance - Leon A.G. Oerlemans; Marius T.H. Meeus (European Regional Science Association (ERSA), 2002)
Recent theoretical developments in organisation science and regional economics have emphasised the importance of networks and geographical proximity for the performance of firms. Empirical evidence on these relationships is scarce, though, especially in regional science. In this paper, we address the following research question: to what extent do firm-specific resources, organisational embeddedness, proximity, and industry factors influence innovative and economic outcomes of innovative firms? We used a theoretical synthesis of regional and organisational science to build a research model that enabled us to derive several hypotheses on the influence of proximity on outcomes, taking other important predictors for performance into account. Our empirical findings confirm the importance of proximity especially for innovative outcomes. Moreover, we found that in particular network relations with buyers and suppliers are conducive for firm performance, whereas other indicators of embeddedness and of internal resources have little impact probably due to substitution effects. Finally, regional as well sectoral R&D spillovers influence outcomes in a positive way.
Keywords: 330